PENCARIAN JALUR TERPENDEK MENUJU POM BENSIN PADA KOTA SEMARANG MENGGUNAKAN ALGORITMA DIJKSTRA BERBASIS SISTEM INFORMASI GEOGRAFIS (GIS) - Teguh Setiadi (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2020)
The search for the shortest route has been applied in many fields to optimize the performance of a system, such as minimizing costs or speeding up a process. The search for the shortest path applied to the roads in many countries has reduced time, travel cost and the inconvenience of the drivers and the passengers. A number of heuristic algorithm approaches have been suggested to reduce the computational time of the shortest path and developed to identify, classify, and compute accurately. The problem to be solved is to find the optimal path in a city’s roads network from the starting path to the target path, involving the computation of roads network to evaluate the nodes’ performance in order to increase the activities of changes during the travel. The Dijkstra’s algorithm is the determination from the starting point to the target point towards the source of problem by considering the weights and the length among nodes. A parameter to consider is travel time so that the preferred shortest path can be recognized and chosen from the starting point to the target location. In this paper, a system for searching the shortest path towards gas stations in Semarang city from the starting point to the target point using geographic information system GIS based Dijkstra’s algorithm is proposed. This system is expected to help users to find the shortest path to the nearest gas stations in Semarang city.